Close-up view of an ongoing merger between the NGC 4839 group and the Coma cluster – a post-merger scenario. Issue 2 (2nd March 2019) - Lyskova, N; Churazov, E; Zhang, C; Forman, W; Jones, C; Dolag, K; Roediger, E; Sheardown, A
ABSTRACT: We study a merger of the NGC 4839 group with the Coma cluster using X-ray observations from the XMM–Newton and Chandra telescopes. X-ray data show two prominent features: (i) a long (∼600 kpc in projection) and bent tail of cool gas trailing (towards south-west) the optical centre of NGC 4839, and (ii) a 'sheath' region of enhanced X-ray surface brightness enveloping the group, which is due to hotter gas. While at first glance the X-ray images suggest that we are witnessing the first infall of NGC 4839 into the Coma cluster core, we argue that a post-merger scenario provides a better explanation of the observed features and illustrate this with a series of numerical simulations. In this scenario, the tail is formed when the group, initially moving to the south-west, reverses its radial velocity after crossing the apocenter, the ram pressure ceases and the ram pressure-displaced gas falls back towards the centre of the group and overshoots it. Shortly after the apocenter passage, the optical galaxy, dark matter, and gaseous core move in a north-east direction, while the displaced gas continues moving to the south-west. The 'sheath' is explained as being due to interaction of the re-infalling group with its own tail of stripped gas mixed with the Coma gas. In this scenario, the shock, driven by the group before reaching the apocenter, has already detached from the group and would be located close to the famous relic to the south-west of the Coma cluster.